POTENSI PELANGGARAN HAK ATAS PROPERTI PRIVAT DALAM PEMBANGUNAN FASILITAS PUBLIK (Kasus Pembangunan Bandara Internasional Kulonprogo) - Rahmad Hidayat (Journal of Governance, 2017)
this paper tries to explore deeply about the potential of violation of citizens’ economic, social, and cultural rights by state (government) in the public infrastructure building project. One of EcoSoC rights that potential to be violated is right to private property i.e. individual house and land. Such rights violation is manifested in the form of forced eviction conducted by government to take over the citizens’ asset and land that defined as a site or location for building certain public facilities. The construction of Kulonprogo International Airport in Yogyakarta is positioned as the main object of analysis. To find out the right answer, I use a case study approach while utilizing the case of construction of Lombok International Airport in 2006-2011 as a comparison.